Analisis Bahasa Indonesia pada Laporan Hasil Kegiatan Penerapan Perangkat Pembelajaran (P3) - Luci Fitri; Didi Yulistio; Gumono Gumono (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
This study aims to describe the use of Indonesian in the Report on the Activities of the Application of Learning Tools (P3) of Indonesian Language and Literature Study Program Students STKIP PGRI Lubuklinggau. The research method used is a qualitative method with the type of descriptive qualitative research. Data collection techniques in this study were documentation techniques. Data analysis techniques by data reduction, data presentation, and conclusions. The results showed that the analysis of the Indonesian language in the Learning Activity Application Reports (P3) there were errors in the use of spelling in this study as many as 831 data quotations were obtained. Word selection errors in this study were 366 citations of data obtained. Ineffective Kalimat obtained 516 citations of data. Based on the results of the study it can be concluded if the use of Indonesian in the P3 report (Application of Learning Tools) is still lacking, so that further guidance is needed so that the future use of Indonesian can be better. Keywords: Language Analysis, Reports, Application of Learning Tools (P3)